Painting as a Fundamental Discipline in the Professional Training of Future Artists of Fine and Decorative Arts in Institutions of Higher Education - Krulyk, Bohdan (Pedagogical Discourse, 2024)
The article examines painting as one of the basic and universal tools in the training of future artists of fine and decorative arts and as an educational discipline in the context of art education in Ukraine, in particular on the example of the study of this discipline by graduates of the department of technological and professional education and decorative arts of Khmelnytskyi National University; the professional competences that are formed during the mastering of painting and the program results according to the Standard of Higher Education are determined; the purpose, subject and tasks of the discipline «Painting» are determined; the main methods and technologies of the teaching process in the discipline «Painting» are defined; practical classes are highlighted as the most effective form and natural image as the leading method of work during mastery of painting by students; note the sections of the content of the educational discipline «Painting» and their content with the topics of practical tasks; gouache is singled out as the optimal material for the realization of natural productions in the teaching of pictorial writing; the importance of accompanying practical tasks with the performance of short-term sketches to solve specific pictorial problems is emphasized; methods of control and revision as a control measure characteristic of artistic disciplines are considered; the close interdisciplinary connections of painting are emphasized; the discipline «Decorative painting» is selected as a related discipline, during which the study of painting in the broad sense continues within the professional training of specialists in the artistic direction; the importance of studying the discipline «Painting» in the system of training a future specialist in fine and decorative arts is substantiated.